USM, BU COME TOGETHER TO CELEBRATE LEARNING - MPRC, Pusat Media & Perhubungan Awam (USM, 2017)
USM, PENANG, 31 March 2017 – Universiti Sains Malaysia (USM) and Bournemouth University (BU), United Kingdom recently organised the Global Festival of Learning which represents a wonderful celebration of learning at the Dewan Budaya here.